What we wish we had known before starting a headache clinical registry: insights from the Italo-Brazilian partnership - Grassi, Vanise; Jurno, Mauro Eduardo; Barbanti, Piero (Headache Medicine, 2025)
Abstract Headache registries have emerged as a logical solution for bridging the gap between what we know and what we do, empowering disease awareness, enhancing knowledge and facilitating personalized management. The role of headache registries in expanding our understanding of patients’ journeys, sociodemographic characteristics, endophenotypes, treatments and healthcare resource utilization is well documented around the world. This perspective article will explore some practical ideas to develop a headache clinical registry from the ground up, through the original contributions of Italian and Brazilian registries.